FAKTOR-FAKTOR PENGGERAK NILAI PERUSAHAAN RETAIL DI BEI: Dividen, Pemilikan Institusional, dan Praktik Manajemen Laba (2018-2022) - Saragih, Muhammad Rizal; Rusdi, Rusdi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to analyze and test the dividend policy, institutional ownership and earnings management on company value. The type of research used in this study is a type of quantitative research with a causal associative approach, and the source used is secondary data in the form of annual reports on retail sector sub for 5 (five) periods. The population in this study were companies in the retail sector sub listed on the Indonesia Stock Exchange during 2018-2022 and there were 130 companies. The research sample was selected based on purposive sampling technique by obtaining 19 companies for 5 periods or 130 observation data. To test the hypothesis using the program EViews series 12. Data were analyzed using the method of panel data regression analysis. The results of this study partially show that dividend policy has no effect on company value, institutional ownership has no effect on company value, and earnings management has no effect on company value. Simultaneously the dividend policy, institutional ownership and earnings management have an effect on company value.